2018
DOI: 10.1039/c8ta05015e
|View full text |Cite
|
Sign up to set email alerts
|

Low-valence bicomponent (FeO)x(MnO)1−x nanocrystals embedded in amorphous carbon as high-performance anode materials for lithium storage

Abstract: Nearly uniform monodisperse bicomponent iron manganese oxide, (FeO)x(MnO)1−x nanocrystals encapsulated in amorphous carbon was used as a high-performance anode material for lithium ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…Obviously, the theoretical calculations demonstrated that the charge redistribution on Ti, O, C, and S occurs at the interface between the LTO and rGO as well as around the oxygen vacancies, which induces an interfacial electric‐field effect. Both Li‐ion diffusion kinetics and electron transport can be accelerated by a built‐in charge‐transfer driving force in the electrode, affording superior rate capability of the CT‐rGO@LTO electrode . The computational results agree well with the XPS and Raman analyses.…”
Section: Resultssupporting
confidence: 59%
“…Obviously, the theoretical calculations demonstrated that the charge redistribution on Ti, O, C, and S occurs at the interface between the LTO and rGO as well as around the oxygen vacancies, which induces an interfacial electric‐field effect. Both Li‐ion diffusion kinetics and electron transport can be accelerated by a built‐in charge‐transfer driving force in the electrode, affording superior rate capability of the CT‐rGO@LTO electrode . The computational results agree well with the XPS and Raman analyses.…”
Section: Resultssupporting
confidence: 59%
“…A lot of important work on exible-based energy storage devices has been reported. [1][2][3][4] As the exible or wearable electronics are usually closely attached to human body, one would expect the exible batteries to have higher safety and environmental standards than other batteries. In this regard, aqueous electrolyte based zinc ion batteries (ZIBs) have drawn a lot of interest not only because they are highly reliable and environmentally friendly, but also because of the abundance of the raw materials, such as Zn sources.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve energy density of LIBs, many anode materials, especially metal oxides (such as SnO 2 , Sb 2 O 3 , Fe 2 O 3 , TiO 2 , and Bi 2 O 3 ) with large reversible Li + storage capacities, have been studied. [6][7][8][9][10] By virtue of its high specific capacity (theoretically 1109 mAh g À 1 ), Sb 2 O 3 has been investigated as a promising anode for LIBs based on conversion and alloying reactions. [11,12] However, the rapid capacity fading and poor reversibility of Sb 2 O 3 are observed initially because of large volume changes upon cycling.…”
Section: Introductionmentioning
confidence: 99%